Characteristics and Properties of TiO2/EP-PU Composite. (9th December 2015) - Yufei, Chen; Zhichao, Li; Junyan, Tan; Qingyu, Zhang; Yang, Han
Abstract : Polymer matrix of EP-PU was prepared by epoxy resin which was polyurethane toughened, and TCA201 coupling agent was used to modify nano-TiO2, and TiO2 /EP-PU composite was synthesized using EP, PU, and TCA201-TiO2 . The results of SEM and TEM showed that the surface of TiO2 was coated with TCA201 coupling agent through the bonding between the hydroxyl of nano-TiO2 particle and coupling agent molecules, the interaction would be beneficial to improve compatibility of inorganic and organic phases, and TCA201-TiO2 would disperse evenly in composite and improve performance of composite materials. The mechanical properties, thermal stability, dielectric properties, and breakdown strength of composites were investigated by electronic tensile machine, TGA, dielectric spectrum, and CS2674C type voltage tester. The results indicated that appropriate amount of TCA201-TiO2 could improve mechanical properties, the shear strength of 3 wt%-TiO2 /EP-PU reached the maximum value at 27.14 MPa, its thermal decomposition temperature was 397.82°C, enhanced 17.48°C more than that of EP-PU matrix, and its dielectric constant( ε ) and dielectric loss (tan ⁡ δ ) showed 4.27 and 0.02, respectively. Its breakdown field strength was 14 kV/mm. Its performance met the requirement of dielectric materials.